Enhancing students’ learning interest and achievement through interactive animated video media - Fitri Nurjanah; Ali Muhtadi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
This study examines the effects of interactive animated video-based learning media that integrate sequential visual illustrations with interactive elements, such as quizzes and immediate feedback, within a Discovery Learning approach, on junior high students' learning interest and learning outcomes in Islamic Religious Education (PAI), and determines the magnitude of this effect. A quantitative, quasi-experimental design was used, involving 160 ninth-grade students divided into a control class (IX.3) and an experimental class (IX.4), each with 29 students. Pretests and post-tests were used to gauge learning outcomes; a questionnaire was also used to gauge learning interest. Simple linear regression and an independent-samples t-test were used to evaluate all data. Results show that every media significantly influenced learning interest and learning outcomes (sig. = 0.001 and 0.010, p < 0.05), contributing 22.5% and 19.8%, respectively, in each medium category. This confirms that every media is a practical, low-infrastructure instructional innovation for procedural material such as Hajj and Umrah.